1986
DOI: 10.1177/34.2.2418103
|View full text |Cite
|
Sign up to set email alerts
|

Immunological characteristics and histological distribution of human hair fibrous proteins studied with anti-hair keratin monoclonal antibodies HKN-2, HKN-4, and HKN-6.

Abstract: By use of a mouse hybridoma technique, monoclonal antibodies were produced against hair fibrous proteins, which were extracted from normal human hairs. Three monoclonal antibodies, designated as HKN-2, HKN-4, and HKN-6, were chosen and used to investigate the immunological characteristics of hair fibrous proteins. Epidermal fibrous proteins were also extracted from human sole callus horny materials. Hair or epidermal fibrous proteins were electrophoretically separated on polyacrylamide gels with sodium dodecyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 18 publications
4
20
0
Order By: Relevance
“…Previously described antibodies raised against hard keratins of hair and/or nail did either cross-react between representatives of both groups of cytokeratins [4,23,30,34,35,42,69] or, when apparently specific for trichocytic cytokeratins (e.g. Previously described antibodies raised against hard keratins of hair and/or nail did either cross-react between representatives of both groups of cytokeratins [4,23,30,34,35,42,69] or, when apparently specific for trichocytic cytokeratins (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously described antibodies raised against hard keratins of hair and/or nail did either cross-react between representatives of both groups of cytokeratins [4,23,30,34,35,42,69] or, when apparently specific for trichocytic cytokeratins (e.g. Previously described antibodies raised against hard keratins of hair and/or nail did either cross-react between representatives of both groups of cytokeratins [4,23,30,34,35,42,69] or, when apparently specific for trichocytic cytokeratins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In fetal development, the clusters of hair follicle and nail germ cells appear to emerge from a subset of early epidermal keratinocytes (for reviews see [S, 51, 71, 72]), and this differentiation of cell shape and character seems to be accompanied by a change from early epidermal cytokeratins [5,12,24,39,491 to the trichocyte-specific cytokeratins. Biochemical analyses of cytoskeletal proteins of trichocytes of hair follicles or of mature hair structures, and also immunocytochemistry using antibodies raised against hair-type (trichocytic) cytokeratins [4,23,30,31,34,35,421, have suggested that synthesis of trichocytic cytokeratins and synthesis of epithelial cytokeratins are mutually exclusive, although they have not proved it. Biochemical analyses of cytoskeletal proteins of trichocytes of hair follicles or of mature hair structures, and also immunocytochemistry using antibodies raised against hair-type (trichocytic) cytokeratins [4,23,30,31,34,35,421, have suggested that synthesis of trichocytic cytokeratins and synthesis of epithelial cytokeratins are mutually exclusive, although they have not proved it.…”
Section: Introductionmentioning
confidence: 99%
“…Immunological studies have indicated the occurrence of common epitopes in epithelial and trichocytic cytokeratins (e.g. [5,26,34,38,39,47,741). Moreover, amino acid sequence comparisons between representatives of either subfamily of sheep wool trichocytic a-keratins and the epithelial cytokeratins have revealed that they are homologous in the a-helical rod domain, but differ considerably in the head and tail domains, including more cysteine and proline residues [12, 15, 59, 72, 731. Probably due to the homologies and similarities between the epithelial and trichocytic cytokeratins and the wellknown cellular complexity of the hair follicle, as revealed by light and electron microscopy (for reviews, see, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[37-39, 57, 64]), the available immunocytochemical data are difficult to interpret. Recently some monoclonal antibodies to " hair fibrous proteins ", i.e., presumably trichocytic cytokeratins, have been described [38,391. Some of these react not only with the hair follicle cortex and medulla but also with the cuticle, whereas others react with these hair-forming cells as well as with certain cells of the inner and outer root sheath.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells of the present case were positively stained with HKN-2, HKN-4, HKN-5 (8,9) and BKN (10, 11). These staining patterns resemble those ofBCE.…”
Section: Histopathologymentioning
confidence: 92%